PENGARUH PEMBERIAN WORTEL KUKUS TERHADAP KADAR HEMOGLOBIN PADA REMAJA IN PONDOK TAHFIDZ AL FATIH, SINTANG REGENCY - Hearty Efifania Ose Payon (Prosiding Seminar Nasional Indonesia, 2025)
Anemia is a problem that often occurs, especially in teenage girl. Anemia is defined as a condition when the concentration level of hemoglobin in blood is low, or the low of hematocrit.Besade in the survey in Girls Dormitory of Abim, Kediri in 2015, there 5 teenage girl no anemia (22,7%), 3 teenagers having anemia weight (13,6%), 6 teenagers level that could be categorized into mild-anemia(27,2%),8 teenagers girls that could be categorized into light anemia(36,3). Carrots contain high-level of iron and vitamin C which have role as the former of hemoglobin level in blood. Steamed carrots release beta carotene that hinders the vitamin absorption inside body. By releasing beta carotene, the iron and vitamin absorption will be better. The objection of this research is to know the influence of steamed carrot administration toward hemoglobin of the teenagers with anemia in Girls Pondok Tahfidz Al Faith Sintang 2024 .Objective: determine the effect of steamed carrot consumption on hemoglobin levels in adolescents with anemia at Pondok Tahfidz Al Faith Sintang in 2024. Research Method: Design of this research was pre-experiment. The researched population was all teenagers having anemia who do not consume blood-enhancing drugs in Girls Pondok Tahfidz Al Faith Sintang 2024 . This research was conducted on 17 people with technique of total population. The instrument was testing tool GCHb and observation sheet. The finding then was analyzed by using Wilcoxon test. Research Results: The result of pretest showed that most respondents (52.9%) which were 9 respondents, had hemoglobin level that could be categorized into mild-anemia. While the result of post-test showed that 8 respondents (47.1%) had hemoglobin level that could be categorized into light anemia. On the analysis result, there was gotten P- Value 0.001< α (0.05), thus H0 was rejected and H1 was accepted. It could be concluded that there is influence in the administrating of steamed-carrot toward hemoglobin level of teenagers with anemia in Girls Pondok Tahfidz Al Faith Sintang 2024. Suggestion: Based on this research, it is expected that teenagers could use alternative non pharmacological cure by steamed-carrot to increase the level of hemoglobin in blood.